INTERNATIONAL LAW STUDY ON PATIENT RIGHTS AND PROTECTION IN THE ERA OF GLOBALISATION - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Adisam Publisher, 2025)
This study of international law highlights the rights and protection of patients in the era of globalisation, focusing on the responsibilities of the state and health institutions and the harmonisation of health regulations between countries. The study emphasises the importance of international treaties and conventions such as the Universal Declaration of Human Rights in guaranteeing the right to health. However, implementation at the national level is still inconsistent due to factors such as limited resources and social injustice. In conclusion, the protection of patients' rights in the era of globalisation requires a multilateral approach, global collaboration, and technical and financial support to ensure the implementation of international obligations and fair and equitable health protection.